Enhancement of therapeutic efficacy of Brinzolamide for Glaucoma by nanocrystallization and tyloxapol addition - Shuya Masuda; Shiho Yano; Tomohisa Tadokoro; Hiroko Otake; Noriaki Nagai (Journal of Pharmaceutical Health Care and Sciences, 2024)
Abstract Background Brinzolamide (BRI) suspensions are used for the treatment of glaucoma; however, sufficient drug delivery to the target tissue after eye drop administration is hampered by poor solubility. To address this issue, we focused on nanocrystal technology, which is expected to improve the bioavailability of poor-solubility drugs, and investigated the effect of BRI nanocrystal formulations on corneal permeability and intraocular pressure (IOP)-reducing effect. Methods BRI nanocrystal formulations were prepared by the wet-milling method with beads and additives. The particle size was measured by NANOSIGHT LM10, and the morphology was determined using a scanning probe microscope (SPM-9700) and a scanning electron microscope (SEM). Corneal permeability was evaluated in vitro using a Franz diffusion cell with rat corneas and in vivo using rabbits, and the IOP-reducing effect was investigated using a rabbit hypertensive model. Results The particle size range for prepared BRI nanocrystal formulation was from 50 to 300 nm and the mean particle size was 135 ± 4 nm. The morphology was crystalline, and the nanoparticles were uniformly dispersed. In the corneal permeability study, BRI nanocrystallization exhibited higher corneal permeability than non-milled formulations. This result may be attributed to the increased solubility of BRI by nanocrystallization and the induction of energy-dependent endocytosis by the attachment of BRI nanoparticles to the cell membrane. Furthermore, the addition of tyloxapol to BRI nanocrystal formulation further improved the intraocular penetration of BRI and showed a stronger IOP-reducing effect than the commercial product. Conclusions The combination of BRI nanocrystallization and tyloxapol is expected to be highly effective in glaucoma treatment and a useful tool for new ophthalmic drug delivery.